Population mobility and indigenous peoples in Australasia and North America - Taylor, J. (John), 1953-; Bell, Martin, 1949- (Routledge research in population and migration, 2004)
Focusing on the four 'New World' countries - Australia, New Zealand, Canada and the United States - this book explores key themes and issues in indigenous mobility.